Review of the species of the Cirolana ‘parva-group’ (Cirolanidae: Isopoda: Crustacea) in Indonesian and Singaporean waters - Sidabalok, Conni M.; Bruce, Niel L. (Zootaxa, 2017)
Ten species of the Cirolana ‘parva-group’ are recorded from shallow water in-shore habitats in the Indo-Malaya region, with five species from both Indonesia (Lombok, North Sulawesi, Maluku and West Papua) and Singapore, four species are from Indonesia only; with only one species locally endemic in Singapore. Three new species are described and Cirolana arafurae Bruce, 1986, Cirolana improceros Bruce, 1986 and Cirolana stenoura Bruce, 1986 are redescribed. A key to Cirolana ‘parva-group’ species found in Indonesia and Singapore is given.